Classification of Mandarin Chinese simple adjectives : a scale-based analysis of their quantitative denotations - Lin, Jingxia (2018)
This work provides an analysis of the quantitative denotations of simple adjectives (base adjectival forms) in Mandarin Chinese following recent analyses of the ‘scale structure’ associated with English adjectives. Against a widely accepted assumption that simple adjectives unitarily denote an unbounded property, we assume that the property of boundedness in adjectives is situated in the notion of gradability, and identify a group of simple adjectives that are actually bounded. We further provide a finer-grained classification of Chinese simple adjectives based on the different scale structures associated with individual adjectives: non-scale adjectives, open-scale adjectives, lower-closed-scale adjectives, upper-closed-scale adjectives and totally-closed-scale adjectives. Each type is linguistically distinguishable in natural Chinese data. Our classification provides a unified account of the distinctive syntactic and semantic characteristics of individual adjectives that cannot be explained by previous studies. This study also demonstrates a cross-linguistic and cross-categorical application of the scale-structure-based analysis.